Cardiac aging - Rabinovitch, Peter; Chiao, Ying Ann (Henry Stewart Talks, 2016)
Cardiac aging in human and animal models, Molecular mechanisms for cardiac aging, Recent advances on potential interventions for cardiac aging, Future perspectives of cardiac aging interventions